The Church in a Communist State: Justin Popovic (1894–1979) and the Struggle for Orthodoxy in Serbia/Yugoslavia - Vukic, Neven (A journal of church and state, 2021)
Justin Popovic (1894–1979) is a saint of the Serbian Orthodox Church (henceforth SOC) and one of its most accomplished theologians. He was born in the southern Serbian town of Vranje, into a priestly family, and was given the name Blagoje. Shortly after completing his nine-year education in Belgrade, he served as a medic during the First World War. In 1916, Popovic was tonsured as a monk in Shkoder, Albania, taking on the monastic name Justin, after the second-century apologist St. Justin Martyr. Within the same year, he was first transferred to St. Petersburg for further education, and upon the outbreak of...